'But I can do the job': examining disability employment practice through human rights complaint cases. Issue 9 (20th October 2016) - Darcy, Simon; Taylor, Tracy; Green, Jenny
Abstract: Natural data on the Australian Human Rights Commission's website outlining the complaint cases generated from Disability Discrimination Act, 1992 (DDA) were used to examine the social construction of disability employment discrimination. Using a social model and human rights citizenship lens, some 987 complaint cases were analysed to assess the prevalence of disability discrimination in employment, and its relationship to the types of disability, gender, entity undertaking the actions and organisational context. Of all complaint cases across the Australian Human Rights Commission's operations, by far the largest proportion involves disability discrimination. Within the disability discrimination complaint cases, employment makes up the greatest proportion of these cases. In examining the patterns of discrimination seven major themes emerged involving: distinctive patterns across disability type; access to premises; human resource mismanagement; selection of new employees; integration of assistive technology; perception of cost of disability inclusions; and inflexible organisational workplace practices. The discussion examines the underlying reasons for the emergent themes where employers misunderstood key legal concepts that underpin the DDA including: unjustifiable hardship; inherent requirements; reasonable adjustment; direct; and indirect discrimination. The paper concludes by discussing the implications of the findings as a way of understanding the social construction of disability discrimination in employment to signal ways to better develop inclusive organisational practice.